SOCIAL MEDIA LITERACY AND FAKE NEWS ACUMEN: A STUDY ON THE LOCUS OF YOUTH IN COIMBATORE CITY - K. B, Sankaranarayanan; Kadeswaran, S; R, Jayaseelan (International Journal of Research -GRANTHAALAYAH, 2023)
Many studies have questioned to what degree of higher media literacy can help fight the flow of misinformation in social media. How can social media literacy help to fight against misinformation and maintain digital hygiene? Conventional media literacy is the ability to distinguish fact from opinion, and to comprehend how media can be used to influence people. Facts are truthful reports of when, where, why and how the event has happened or what exists, and opinions are the interpretations of the meaning or impact, usually from an individual's point of view Kerry Gallagher & Magid (2017). The study analyzed the contents and competencies, required for an individual to become a social media literate and thereby distinguish fake and fact news in social media using a conceptual framework developed by Cho et. al. (2022). Results reveals that there is no “One size fits all” solution to develop media literacy among youth, but more initiatives and awareness programmes can be conducted and included in curriculum to educate and make aware on the pros and cons of using social media and also various tools available for fact checking in the internet.